Low coverage of COVID-19 vaccines in Africa: current evidence and the way forward - Lukman Lawal; Munira Aminu Bello; Tonderai Murwira; Clement Avoka; Shamsuddeen Yusuf Ma'aruf; Imoetin Harrison Omonhinmin; Pamela Maluleke; Christos Tsagkaris; Helen Onyeaka (Human Vaccines & Immunotherapeutics, 2022)
Disparities in COVID-19 vaccine coverage across the globe have uncovered inequities in global healthcare. While more than half of the population of the developed countries have been fully vaccinated, only a small percentage of the African population has received one vaccine dose so far, a far cry from the global vaccination targets. Furthermore, several low and middle income (LMICs) African countries lack the competence, infrastructure, logistics, and financial resources to mass-vaccinate their populations. This paper highlights the causes and implications of the low COVID-19 vaccine coverage on Africa and the global community, and discusses strategies for restructuring and strengthening COVID-19 vaccination in Africa.